Impacto del proyecto “mejoramiento de la producción y productividad del cultivo de papa y haba en las comunidades de la parroquia san juan, cantón Riobamba, provincia de Chimborazo” implementado por la coordinación de fomento productivo del GAD provincial de Chimborazo en el cantón Riobamba en el desarrollo económico de las comunidades de la parroquia san juan, periodo 2013-2014. - Zúñiga Hernández, Àngel Eduardo (2017)
This project denominated Impact of the project "Improvement of the production and productivity of potato and bean cultivation in the communities of San Juan parish, Riobamba canton, Chimborazo province", implemented by the coordination of Fomento Procuctivo del GAD provincial of Chimborazo in Riobamba Canton; in the economic development of the communities from San Juan parish, period 2013 – 2014. It consists of some chapters, where it describes the characteristics of the performed process as well as the used methodology and the outline of work. They are described below: The first chapter is composed by the frame of reference where it was determined the achievement of the problem approach, objectives, justification and importance of the project. The second chapter delimited the theoretical framework, which consists of the bibliographical revision with theories related to economic development, the study of the Productive Development project carried out by the GAD of the Chimborazo Province and the impact caused on the living conditions of the Households of the communities from San Juan parish, finally, it shows the analysis of economic and social indicators. Chapter III presents the results of the research using secondary sources and the application of the surveys that were distributed among San Juan Parish homes, Riobamba Cantón, which were benefited.